MODELING OF DRUG-DIFFUSION KINETICS OF AMOXICILLIN TRIHYDRATE FROM BUCCAL TABLETS - GOPA ROY BISWAS,; SUTAPA BISWAS MAJEE, (International Journal of Pharma and Bio Sciences, 2015)
The aim of the current investigation is to study the kinetics of drug release pattern from buccal swellable, controlled release tablets of amoxicillin trihydrate. Buccal tablets were prepared with modified gum karaya in 5-20% concentration. Drug release from the formulated amoxicillin trihydrate loaded buccal tablets followed Zero order kinetics resulting in regulated and controlled release for a given time from all the batches. Swelling index increased with increase in concentration of modified gum karaya. The drug release mechanism was confirmed by Korsmeyer-Peppas exponential equation. It was also observed that among the four batches, the tablets with 5-15% modified gum karaya obeyed Fickian diffusion mechanism, whereas the other (20%) showed the relaxation mechanism. Further for proper clarification the data were fitted to Kopcha mathematical model. This finding is supported by evaluation of the ratios of the exponents A/B (i.e., diffusional factor A and erosional factor B) derived from the Kopcha model, which were greater than 1 in all cases. A/B were found to be much higher (35-40) in the tablets with 5-15% of modified gum karaya suggesting that drug release from the buccal tablets is primarily controlled by a Fickian diffusion process . In the buccal tablets with 20 % of modified gum karaya A/B was found to be quite less (24) than the previous batches. Due to the high water affinity of the gum there will be a greater rate of polymer swelling, which is reflected in the drug diffusion mechanism.